2016
DOI: 10.1037/pspa0000050
|View full text |Cite
|
Sign up to set email alerts
|

Maybe holier, but definitely less evil, than you: Bounded self-righteousness in social judgment.

Abstract: Few biases in human judgment are easier to demonstrate than self-righteousness: the tendency to believe one is more moral than others. Existing research, however, has overlooked an important ambiguity in evaluations of one's own and others' moral behavior that could lead to an overly simplistic characterization of self-righteousness. In particular, moral behavior spans a broad spectrum ranging from doing good to doing bad. Self-righteousness could indicate believing that one is more likely to do good than othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 87 publications
(107 reference statements)
5
45
2
Order By: Relevance
“…In contrast, adults typically distinguished among agents; for example, they reported that they were more likely than God or another person to think that good behaviours were acceptable. Adults may have viewed themselves as more moral than other people, consistent with work showing that Western adults value uniqueness (Fromkin & Snyder, 1980) and evaluate themselves more positively than others (Klein & Epley, 2016;Pronin, 2008).…”
Section: Discussionsupporting
confidence: 64%
“…In contrast, adults typically distinguished among agents; for example, they reported that they were more likely than God or another person to think that good behaviours were acceptable. Adults may have viewed themselves as more moral than other people, consistent with work showing that Western adults value uniqueness (Fromkin & Snyder, 1980) and evaluate themselves more positively than others (Klein & Epley, 2016;Pronin, 2008).…”
Section: Discussionsupporting
confidence: 64%
“…Consistent with this hypothesis, recent evidence suggests that "selfrighteousness" -manifested in, for example, the average person rating themselves morally superior to the average person (Tappin & McKay, 2017) -are greater for immoral than moral stimuli (Klein & Epley, 2016. Relatedly, the correlation between individuals' life satisfaction and their self-perception is reportedly stronger if the latter is computed as the distance between individuals' "real" and "undesired" selves vs. between their "real" and "desired" selves (Ogilvie, 1987).…”
Section: Doing Good Vs Avoiding Badmentioning
confidence: 85%
“…Alternatively, people might believe that they are more altruistic than others (i.e., seeing oneself as an altruist among egoists). Prior work suggests that people overestimate their selflessness -especially when comparing themselves to others (Epley & Dunning, 2000;Pronin, 2007;Rempel et al, 1985; but see also Klein & Epley, 2016). As such, beliefs about altruism may feature a motivated bias that places oneself above the average person (Kunda, 1990).…”
Section: Lay Theories Of Altruismmentioning
confidence: 99%